THE EFFECTIVENESS OF VILLAGE FUND UTILIZATION IN SUPPORTING DEVELOPMENT IN ALUE DUA VILLAGE - Wiriani, Erni (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The policy of regional autonomy empowers villages to play a significant role in development, supported by village funds sourced from the national budget. However, concerns arise regarding the potential for corruption in managing these funds. To address this, oversight mechanisms are crucial, alongside regulations such as local regency regulations and ministerial directives. Prioritizing fund usage for infrastructure and community empowerment is key. Continuous supervision and evaluation are necessary to ensure transparency and prevent misappropriation.